ORGANIZATIONAL MECHANISM OF RISK-FREE HEDGING AS A FACTOR OF INCREASING LIQUIDITY OF UKRAINIAN EXCHANGES - KUSTOV, VITALIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes theoretical approaches to the concept of "market maker". It is proposed to use market makers to ensure a continuous flow of liquidity of the exchange. Futures delivery technology has been studied. The schemes of application of futures instruments on elevators are distinguished. Specific examples with data and relevant calculations for trading the same exchange commodity on both low-liquid and highly liquid exchanges are given. Three variants of events are analyzed and conclusions about the high probability of probability of the third option are formulated. Algorithms for executing orders "trader − trader" and "trader − market maker" are considered. It has been proven that one of the methods of solving the problem of market maker risk is the Last Look system. It is determined that the main data transfer protocols between the exchange and its institutional participants can be Fix and Fast data protocols. The advantages and disadvantages of the Fix and Fast data protocols are highlighted. It is determined that the Fix message structure is defined by the protocol and must contain: message header; the length of the body of the message; message type; message body; checksum. It has been found that the Fast protocol is actively implemented on trade sites, but continues to be inferior to the popularity of "classic" Fіх. It is determined that the main efforts are the development of Fast protocol, which aims to eliminate the possibility of delays, and the main changes of Fast protocol, aimed at reducing the volume and speed of data transmission: 1) Fast messages are created in a single standard template special and service symbols, field names and delimiters are excluded at the same time); 2) message fields are arranged in the same order as the template tags; 3) not all data are transferred to Fast, but only data changes. In the process of improvement, it was found that the Fast algorithm has evolved to version 1.2, which is the most common and used by most financial market players and is a standardized protocol for the exchange of market information. Several versions of the open source protocol (Open FAST, Open FAST.NET, and Quick FAST) have been identified.
Keywords: risk-freehedge; exchange; stockexchange instruments; elevator; liquidity; market-maker; futures